EFISIENSI PENGGUNAAN FAKTOR PRODUKSI PADA USAHATANI JAGUNG DI KECAMATAN REMBOKEN KABUPATEN MINAHASA (Studi Perbandingan Peserta dan Bukan Peserta Sekolah Lapang Pengelolaan Tanaman Terpadu) - Carolina B.D. Pakasi; L. Pangemanan; Juliana R. Mandei; Nineteen N.I. Rompas (Sam Ratulangi University, 2011)
The study was designed to analyze the efficiency of production factors between the program and whodo not follow SLPTT program. This study starts from November to December 2010. Data obtained fromprimary and secondary data. Primary data obtained from interviews using a questionnaire to cosumers.Sampling was done by using the method of Sampling Cluster, specifically 3 farmers groups program participantsSLPTT and 3 farmers group who are not participants SLPTT program. The analytical tool used is regressionanalysis Cobb-Douglas model using the program Minitab 15.Results showed that technically, the efficient use of production factors of land, urea fertilizer, seed, laborand herbicides by farmers SLPTT participants and not participants are the same. unless the use of fertilizersponska. Land use has not been efficient because of the percentage increase in corn production is higherthan the percentage increase in land (Ep> 1), the use of urea fertilizer and seed are efficient (0 <Ep <1)while the use of production factors labor and herbicides are not efficient because the additional factor ofproduction will reduce the production of maize (Ep <0). The use of factors of production of fertilizers byfarmers participating ponska SLPTT already efficient while the use of fertilizer by farmers rather than participantsSLPTT inefficient.Economically, the efficient use of production factors by both participants and non-participant farmersSLPTT is the same except for the use of fertilizers ponska. The use of production factors land, urea fertilizer,and seed has not been efficient, while the use of production factors labor and herbicides are not efficient.The use of factors of production of fertilizers by farmers participating Phonska SLPTT has not been efficientwhile the use of factors of production by non-participant farmers SLPTT inefficient.